TINJAUAN PENGGUNAAN UNSUR TRADISIONAL CINA PADA RESTORAN CINA, KAPAL PESIAR GENTING DREAM, RESORT WORLD CRUISES - Iqbal Jasir Fauzy Adya; Zein, Anastasha (Department of Interior Design, Faculty of Engineering, Lancang Kuning University, Indonesia, 2024)
In order to achieve a unique holiday experience for users, cruise ship accommodation facilities try to give a strong impression through their interior appearance. The Genting Dream cruise ship, owned by Resort World Cruises, has the main goal of managing the rich cultural heritage of Asia into the space on board. Several areas of the ship incorporate the characteristics of Asian countries to reinforce the vision of the ship itself. One of them is applied to the typical Chinese food restaurant area - 'Silk Road & Cabaret'. by carrying 'ancient Shanghai' as the concept raised in it. This area is a restaurant that includes food service as well as cabaret entertainment with traditional Chinese cultural characteristics in it. Through a qualitative approach and case study research method, the results of identification and analysis related to the use of several natural motifs and Chinese character symbols that have special meanings are obtained so that they are placed on several interior elements according to the essence contained therein. These traditional Chinese elements have several good meanings related to luck, social status, wealth and prosperity, longevity, and happiness for their users.